Změna zákona o České národní bance jako cesta k měnovému financování? - Michael Kohajda (Acta Universitatis Carolinae. Iuridica, 2020)
In his article, the author deals with the amendment to the Act on the Czech National Bank adopted in the spring of 2020. He examines the process of adopting this amendment and also the reasons for its adoption from the point of view of monetary financing. He examines whether the consequence of this amendment potentially could not result in enabling monetary financing by the Czech central bank. Furthermore, his article also deals with the nature and risks of monetary financing, discusses the difference between direct and indirect monetary financing, the reasons for the ban on monetary financing and the importance of whether monetary financing is carried out directly or indirectly from the perspective of this ban and its reasons. In conclusion, the author evaluates the adopted amendment to the Act that this amendment introduces instruments that could be used for monetary financing, but that the specific use of the instruments is more important, as they can be used for monetary policy purposes or to maintain financial stability, where their use is generally acceptable, but also for the monetary financing, where their use should be prohibited